Odpowiedzi

Najlepsza Odpowiedź!
2010-02-14T22:53:29+01:00
5(x-4)+6y=12-x
(3+x)/2=(2y+10)/4 |*4

5x-20+6y=12-x
6+2x=2y+10

6x+6y=32 |:6
2x-2y=4 |:2

x+y=5i1/3
x-y=2

x=5i1/3-y
5i1/3-y-y=2

x=5i1/3-y
-2y=-3i1/3 |:-2

x=5i1/3-y
y=1i2/3

x=3i2/3


czyli odpowiedź A
1 5 1
2010-02-14T23:01:38+01:00
5(x-4) + 6y = 12-x
(3+x)/2=(2y+10)/4 /*4

5x-20+6y+x=12
6+2x=2y+10

6x+6y=32
2x-2y=4 /*3

6x-6y=12
6x+6y=32
--------------
12x=44
x=3 2/3

6y= 32-6*x
6y = 32-6*11/3
y=10/6=5/3=1 2/3


Odp. a jest poprawna
1 5 1